A method for determining the content of scandium in spray-formed aluminum alloy
By using titration assay and two-step dissolution method in the scandium element content determination method, the existing methods require expensive equipment and incomplete dissolution are solved, and the accurate determination of scandium content in jet-formed aluminum alloy is achieved, reducing costs and improving precision.
Patent Information
- Application Number
- CN202210556422.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-05-20
AI Technical Summary
The existing scandium element content measurement methods require expensive equipment, and the solution method is not completely dissolved when processing aluminum alloys containing silicon and titanium, resulting in abnormal test results.
A scandium element content determination method of jet-formed aluminum alloy is adopted. The precipitate problem is solved by boiling distilled water through the titration determination method and the two-step dissolving method, thereby avoiding the use of high-priced equipment.
Accurate measurement of jet-formed aluminum alloys with scandium content of 0.2-2.0% is achieved, which simplifies equipment requirements, reduces costs, and improves measurement precision and repeatability.
Smart Images

Figure BDA0003655104410000081 
Figure BDA0003655104410000091 
Figure BDA0003655104410000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scandium element content determination, and in particular to a method for determining the scandium element content of a spray-formed aluminum alloy. Background Art
[0002] With the development of aluminum alloy material research, transition elements and rare earth elements are added to aluminum alloys to improve some properties. Scandium has the functions of both rare earth elements and transition metal elements. Its main functions are to prevent abnormal recrystallization and refine grains, strong aging strengthening to improve strength, excellent thermal stability, etc., and has been widely used and studied. As the aerospace field has higher and higher requirements for the toughness of aluminum alloys, scandium is also more widely used in the composition ratio of commonly used aerospace aluminum alloys such as 2 series, 5 series, and 7 series.
[0003] Spray forming technology is an advanced material forming process developed based on rapid solidification technology. Its basic principle is that the molten alloy is atomized by high-pressure gas spray in an inert atmosphere and flies at high speed along the axis of the nozzle. Before the atomized droplets are completely solidified, they are deposited on the receiver, and finally form a deposited billet after impact, adhesion, and solidification. Due to the fast cooling rate, the migration of alloy elements is confined to the grain range, and macro-segregation under the casting process will not occur. It can also inhibit grain coarsening and greatly improve material properties. This process is not limited by alloy content, greatly broadens alloy formulas and specifications, and is currently the most advanced solidification technology after semi-continuous casting. It is especially suitable for the preparation of high alloy content and large-scale ingots.
[0004] At present, according to the standard GB / T 20975.27-2018 "Chemical Analysis Methods for Aluminum and Aluminum Alloys Part 27: Determination of Cerium, Lanthanum and Scandium Contents by Inductively Coupled Plasma Atomic Emission Spectrometry", the "Inductively Coupled Plasma Atomic Emission Spectrometry" can be used to determine the scandium content in aluminum alloys, with a measurement range of 0.0002-0.5%. The "Inductively Coupled Plasma Atomic Emission Spectrometry" required in the standard requires the use of "Inductively Coupled Plasma Atomic Emission Spectrometer ICP-AES" equipment, and ordinary companies cannot afford the expensive equipment. When dissolving aluminum alloys containing scandium by ordinary solution method / titration method, the addition of silicon and titanium intermediate alloy elements will cause the alloy to fail to dissolve or incompletely dissolve, resulting in abnormal test results. The method provided in this standard often has precipitation problems after the solution preparation is completed. Summary of the invention
[0005] The present invention provides a method for determining the scandium content of a spray-formed aluminum alloy, which can determine the scandium content of the chemical composition of the spray-formed aluminum alloy with a scandium content of 0.2-2.0%.
[0006] The present invention adopts the following technical solutions.
[0007] A method for determining the scandium content of a spray-formed aluminum alloy, the method comprising the following steps:
[0008] (1) Weigh the aluminum alloy chip sample A and measure its mass twice independently, and take the average value W;
[0009] (2) Weigh a sample B with a known scandium content of the same mass as the average value W and perform a control test;
[0010] (3) When the silicon content of sample A is ≤0.1% and the titanium content is ≤0.01%, place sample A in a beaker, add hydrochloric acid solution in portions, cover with a watch glass, and after the reaction stops, add hydrogen peroxide solution, heat until completely dissolved, evaporate to nearly dryness, add water, shake well, add ascorbic acid, triethanolamine, and sulfosalicylic acid and shake well; test the pH value of the sample solution, adjust the pH, add two drops of xylenol orange indicator, and titrate with a reagent of concentration C until the color changes from purple-red to bright yellow as the end point; read the volume V of the reagent used to calculate the content of scandium;
[0011] When the silicon content in sample A is ≥0.1% and the titanium content is ≥0.01%, add sodium hydroxide solution to sample A, cover with a watch glass, wait for the reaction to be complete, heat until large bubbles appear, add hydrochloric acid solution, add hydrogen peroxide dropwise, heat until completely dissolved, evaporate to near dryness, add water, shake well, add ascorbic acid, triethanolamine, and sulfosalicylic acid, shake well; test the pH value of the sample solution, adjust the pH value, add two drops of xylenol orange indicator, and titrate with a reagent of concentration C until the color changes from purple-red to bright yellow as the end point; read the volume V used for the reagent to calculate the content of scandium;
[0012] (4) Calculation and analysis results: ω(Sc) = (C × V × M ÷ W) × %, M: molar mass of scandium.
[0013] Furthermore, the thickness of the aluminum alloy chips in step (1) is not greater than 1 mm.
[0014] Furthermore, the storage time after adding ascorbic acid in step (3) is ≤ 1 h.
[0015] Furthermore, in the step (3), the mass ratio of ascorbic acid, triethanolamine and sulfosalicylic acid is 1:15-25:1-3.
[0016] Furthermore, in step (3), the pH value is adjusted to 2.0-2.2.
[0017] Furthermore, the reagent used for titration in step (3) is a standard solution of disodium ethylenediaminetetraethylamine (EDTA 0.01 mol / L) or a standard solution of disodium ethylenediaminetetraethylamine (EDTA 0.005 mol / L).
[0018] Furthermore, the standard solution of disodium ethylenediaminetetraethylamine (EDTA 0.01 mol / L): weigh 3.7226 g of standard disodium ethylenediaminetetraethylamine in a 250 ml beaker, add boiling distilled water and heat to dissolve, and become transparent, transfer to a 1000 ml volumetric flask, dilute to the scale with boiling distilled water, and mix evenly; the standard solution of disodium ethylenediaminetetraethylamine (EDTA 0.005 mol / L): weigh 1.8613 g of standard disodium ethylenediaminetetraethylamine in a 250 ml beaker, add boiling distilled water and heat to dissolve, and become transparent, transfer to a 1000 ml volumetric flask, dilute to the scale with boiling distilled water, and mix evenly.
[0019] Furthermore, the determination method is suitable for determining the scandium content in aluminum and aluminum alloys, and the determination range is scandium: 0.20%-2.0%.
[0020] The beneficial effects of the present invention are:
[0021] (1) The present invention provides a "titration method" that can avoid the use of expensive testing equipment; the present invention provides a "two-step dissolution" method that eliminates the influence of silicon and titanium elements on the test results; in the solution preparation process, "boiled distilled water" is used instead of ordinary distilled water to solve the problem of precipitation after the solution preparation is completed;
[0022] (2) The improved titration method is used to determine the scandium content in the spray-formed aluminum alloy: the determination range is 0.2-2.0%, and the use of an ordinary voltage-stabilized power supply electric furnace and a acidity meter can meet the determination equipment requirements, which is simple, convenient and low-cost; and within the measurement range of 0.2-0.5%, under the corresponding precision requirements and repeatability conditions, the determination values of multiple independent measurement results obtained, the repeatability limit r all meet the corresponding repeatability limit requirements in the standard; the difference between multiple measurement and analysis results between laboratories meets the allowable difference requirements; within the measurement range of 0.5-2.0%, there are no corresponding precision, repeatability and allowable difference requirements, and the actual measured values are provided. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with examples.
[0024] A method for determining the scandium content of a spray-formed aluminum alloy comprises the following steps:
[0025] The main alloy elements are spray-formed into aluminum alloy according to the ratio of scandium Sc (0.2-2.0%) and Al (balance).
[0026] 1. Use titration method to determine the scandium content of spray-formed aluminum alloy chips. Range: Suitable for the determination of scandium content in aluminum and aluminum alloys. The determination range is scandium: 0.20%-2.0%.
[0027] 2. Implementation process: After the sample is dissolved, in a dilute hydrochloric acid medium, within a certain acidity range, use xylenol orange as an indicator and titrate with disodium ethylenediaminetetraethylamine standard solution to measure the scandium content in aluminum and aluminum alloy.
[0028] 3. Reagents
[0029] 3.1 Hydrogen peroxide (ρ=1.10 g / mL), high purity.
[0030] 3.2 Hydrochloric acid (ρ=1.19 g / mL), high purity.
[0031] 3.3 Ammonia water (ρ=0.9 g / mL), high purity.
[0032] 3.4 Ethylenediaminetetraethylamine disodium, standard.
[0033] 3.5 hydrochloric acid (1+1).
[0034] 3.6 Sodium hydroxide (200g / L).
[0035] 3.7 Xylenol orange indicator (1 g / L).
[0036] 3.8 Ascorbic acid, high purity.
[0037] 3.9 Sulfosalicylic acid (100g / L), high purity.
[0038] 3.10 Triethanolamine (1+1), high purity.
[0039] 3.11 Ammonia water (1+1).
[0040] 3.12 Boil distilled water
[0041] 3.13 Ethylenediaminetetraethylamine disodium standard solution (EDTA 0.01 mol / L): Weigh 3.7226 g of standard ethylenediaminetetraethylamine disodium into a 250 ml beaker (3.4), add boiling distilled water and heat to dissolve until transparent, transfer to a 1000 ml volumetric flask, dilute to scale with boiling distilled water, and mix well. (No calibration required)
[0042] 3.14 Ethylenediaminetetraethylamine disodium standard solution (EDTA 0.005 mol / L): Weigh 1.8613 g of standard ethylenediaminetetraethylamine disodium into a 250 ml beaker (3.4), add boiling distilled water and heat to dissolve until transparent, transfer to a 1000 ml volumetric flask, dilute to scale with boiling distilled water, and mix well. (No calibration required)
[0043] The specimens were processed into chips with a thickness not exceeding 1 mm.
[0044] A method for determining the scandium content of a spray-formed aluminum alloy comprises the following steps:
[0045] (1) Weigh 0.5 g or 1.0 g of sample A (accurate to 0.001 g). Measure the mass twice independently and take the average value W.
[0046] (2) Controlled trials
[0047] Weigh the same amount of sample B (with known scandium content) as sample A and carry out a control experiment together with sample A.
[0048] (3) Determination
[0049] When the silicon content of sample A is ≤0.1% and the titanium content is ≤0.01%, place sample A in a 500ml beaker, add 10ml of hydrochloric acid (3.5) in portions, cover with a watch glass, and after the reaction stops, add a few drops of hydrogen peroxide (3.1), slowly heat until completely dissolved, evaporate to nearly dryness, add 80ml of water, shake well, add 0.2g of ascorbic acid (3.8), 6ml of triethanolamine (3.10), and 3ml of sulfosalicylic acid (3.9), and shake well.
[0050] The solution was left to stand for ≤1h after ascorbic acid was added.
[0051] Test the pH value of the sample solution with an acidometer, adjust the pH value to 2.0-2.2 with hydrochloric acid (3.5) or ammonia (3.11), add two drops of xylenol orange indicator (3.7), and titrate with (EDTA 0.01 mol / L) disodium ethylenediaminetetraethylamine standard solution (3.13) or (EDTA 0.005 mol / L) disodium ethylenediaminetetraethylamine standard solution (3.14) until the color changes from purple-red to bright yellow. Read the volume V of the titrant used and calculate the scandium content.
[0052] For different sample contents, select appropriate EDTA standard solution.
[0053] When the silicon content of sample A is ≥0.1% and the titanium content is ≥0.01%, place sample A in a 100ml polyfluoroethylene beaker or a silver beaker, add 10ml sodium hydroxide (3.6), cover with a watch glass, and after the reaction is complete, heat until large bubbles appear, transfer 30ml of hydrochloric acid (3.5) to a 500ml beaker, add a few drops of hydrogen peroxide (3.1), heat until completely dissolved, evaporate to nearly dryness, add 50ml of water, shake well, add 0.2g of ascorbic acid (3.8), add 6ml of triethanolamine (3.10), add 3ml of sulfosalicylic acid (3.9), and shake well.
[0054] Adding sodium hydroxide solution helps the sample dissolve in the first step, and adding hydrochloric acid solution helps the sample dissolve in the second step, which is the two-step dissolution method.
[0055] The silicon and titanium elements in sample A are impurity elements in aluminum alloy. The silicon and titanium elements in sample A are "aluminum master alloy silicon" and "aluminum master alloy titanium" added during the production process of aluminum alloy, and are standard elements of aluminum alloy composition.
[0056] Test the pH value of the sample solution with an acidometer, adjust the pH value to 2.0-2.2 with hydrochloric acid (3.5) or ammonia (3.11), add two drops of xylenol orange indicator (3.7), and titrate with (EDTA 0.01 mol / L) disodium ethylenediaminetetraethylamine standard solution (3.13) or (EDTA 0.005 mol / L) disodium ethylenediaminetetraethylamine standard solution (3.14) until the color changes from purple-red to bright yellow. Read the volume V of the titrant used and calculate the scandium content.
[0057] Low or high solution acidity is not conducive to the reaction. Through experiments, the acidity was selected to be pH 2.0-2.2.
[0058] Calculation of analysis results
[0059] ω(Sc)=(C×V×M÷W)×% (1)
[0060] In formula (1):
[0061] C-------------EDTA standard solution, mol / L;
[0062] V-------------the volume of EDTA standard solution consumed, mL;
[0063] M------------Molar mass of scandium, 44.96 g;
[0064] W------------sample weight, g.
[0065] By using the determination method of the present invention, the scandium content in the spray-formed aluminum alloys with four theoretical scandium content ratios of 0.225%, 0.486%, 1.022% and 1.878% was determined.
[0066] After determination, the precision results of multiple measurements, under the measurement repeatability conditions, the measurement values of multiple independent measurement results, the repeatability limit r all meet the corresponding repeatability limit requirements in the standard; the allowable difference meets the corresponding allowable difference requirements in the standard, that is, the measurement precision meets the standard requirements, and this determination method can be used instead of the standard determination method. The measurement results and data analysis are shown in Tables 1, 2, and 3 below:
[0067] Table 1. Ten independent measurement results of four theoretical ratios
[0068]
[0069]
[0070] Note: The control test is a test process and method confirmation conducted by the inspector based on the self-made comparison samples to ensure that no serious deviation occurs during this test. The control test data does not need to be provided every time, but only needs to be confirmed by the inspector that this experiment is the test data recognized by the inspector.
[0071] The repeatability limit r refers to the consistency between the results obtained from multiple consecutive measurements of the same measured quantity. It is the interval in which the difference between the two measurement results under repeatability conditions exists with a probability of 95%. That is, the probability that the difference between the two measurement results falls within the interval r or that this difference is ≤r is 95%.
[0072] Calculation formula: Repeatability limit r = 2.8σ r
[0073] where σ r It refers to the standard deviation under repeatability test conditions.
[0074] Table 2. Standard deviation of ten independent measurements
[0075]
[0076] Table 3. Permissible differences between ten independent measurements
[0077]
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for determining the scandium content of a spray-formed aluminum alloy, characterized in that: The determination method comprises the following steps: (1) Weigh the aluminum alloy chip sample A and measure its mass twice independently, and take the average value W; (2) Weigh a sample B with a known scandium content of the same mass as the average value W and perform a control test; (3) When the silicon content of sample A is ≤0.1% and the titanium content is ≤0.01%, place sample A in a beaker, add hydrochloric acid solution in portions, cover with a watch glass, and after the reaction stops, add hydrogen peroxide solution, heat until completely dissolved, evaporate to nearly dryness, add water, shake well, add ascorbic acid, triethanolamine, and sulfosalicylic acid and shake well; test the pH value of the sample solution, adjust the pH, add two drops of xylenol orange indicator, and titrate with a reagent of concentration C until the color changes from purple-red to bright yellow as the end point; read the volume V of the reagent used to calculate the content of scandium; When the silicon content in sample A is ≥0.1% and the titanium content is ≥0.01%, add sodium hydroxide solution to sample A, cover with a watch glass, wait for the reaction to be complete, heat until large bubbles appear, add hydrochloric acid solution, add hydrogen peroxide dropwise, heat until completely dissolved, evaporate to near dryness, add water, shake well, add ascorbic acid, triethanolamine, and sulfosalicylic acid, shake well; test the pH value of the sample solution, adjust the pH value, add two drops of xylenol orange indicator, and titrate with a reagent of concentration C until the color changes from purple-red to bright yellow as the end point; read the volume V used for the reagent to calculate the content of scandium; (4) Calculation and analysis results: ω(Sc) = (C × V × M ÷ W) × %, M: molar mass of scandium; In the step (3), the mass ratio of ascorbic acid, triethanolamine and sulfosalicylic acid is 1:15-25:1-3; The reagent used for titration in step (3) is a disodium ethylenediaminetetraacetic acid standard solution with a concentration of 0.01 mol / L or a disodium ethylenediaminetetraacetic acid standard solution with a concentration of 0.005 mol / L.
2. The method for determining the scandium content of a spray-formed aluminum alloy according to claim 1, characterized in that: The thickness of the aluminum alloy chips in the step (1) is not greater than 1 mm.
3. The method for determining the scandium content of a spray-formed aluminum alloy according to claim 1, characterized in that: The storage time after adding ascorbic acid in step (3) is ≤1h.
4. The method for determining the scandium content of a spray-formed aluminum alloy according to claim 1, characterized in that: In the step (3), the pH value is adjusted to 2.0-2.
2.
5. The method for determining the scandium content of a spray-formed aluminum alloy according to claim 1, characterized in that: The concentration of the disodium ethylenediaminetetraacetic acid standard solution is 0.01 mol / L: 3.7226 g of the standard disodium ethylenediaminetetraacetic acid is weighed into a 250 ml beaker, and heated with boiling distilled water to dissolve until it becomes transparent, and then transferred into a 1000 ml volumetric flask, diluted to the scale with boiling distilled water, and mixed evenly; the concentration of the disodium ethylenediaminetetraacetic acid standard solution is 0.005 mol / L: 1.8613 g of the standard disodium ethylenediaminetetraacetic acid is weighed into a 250 ml beaker, and heated with boiling distilled water to dissolve until it becomes transparent, and then transferred into a 1000 ml volumetric flask, diluted to the scale with boiling distilled water, and mixed evenly.
6. The method for determining the scandium content of a spray-formed aluminum alloy according to claim 1, characterized in that: The determination method is suitable for determining the scandium content in aluminum and aluminum alloys, and the determination range is scandium: 0.20%-2.0%.
Citation Information
Patent Citations
Method for determining scandium oxide in scandium-zirconium ceramic body
CN112180027A
Method for determining content of silicon element in spray-formed aluminum alloy
CN113295634A